Comparison of sampling methods for next generation sequencing for patients with lung cancer. (10th March 2022) - Kunimasa, Kei; Matsumoto, Shingo; Nishino, Kazumi; Honma, Keiichiro; Maeda, Noboru; Kuhara, Hanako; Tamiya, Motohiro; Inoue, Takako; Kawamura, Takahisa; Kimura, Toru; Maniwa, Tomohiro; Okami, Jiro; et al.
Abstract: Introduction: Success of next generation sequencing (NGS) analysis is becoming indispensable in the treatment of advanced lung cancer. However, the advantages and disadvantages of each sampling method in the NGS analysis have not yet been clarified. Methods: We compared the success rates of NGS analysis, and DNA and RNA yields for transbronchial biopsy (TBB), endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA), computed tomography (CT)‐guided biopsy, fluid sample, and surgical biopsy for NGS analysis in patients through the lung cancer genomic screening project for individualized medicine (LC‐SCRUM)‐Asia, a nationwide NGS screening project. In case, sufficient samples could not be collected by TBB and EBUS‐TBNA, re‐biopsy (genome re‐biopsy) was performed. Results: A total of 223 patients were enrolled and success rates of NGS analysis were not different between samples obtained through TBB, EBUS‐TBNA, and CT‐guided biopsy; however, success rates for fluid samples and surgical biopsy samples were significantly higher than those of other methods. The risk of genome re‐biopsy was higher with TBB for centrally located lesions. CT‐guided biopsy yielded more samples but had a lower success rate for analysis of RNA‐based NGS than TBB. Conclusions: TBB is the mainstay of sampling methods, but for centrally located lesions, EBUS‐TBNA may be a better strategy. For CT‐guided biopsy, the success rate of RNA‐based NGS analysis is low. Fluid samples are expected to yield successful results as surgical biopsy samples, but the latter are better for sample preservation. Determining the optimal method for genome biopsy for each case is important. Abstract : We compared sampling methods for the successful pre‐treatment NGS analysis in LC‐SCRUM‐Asia in patients with advanced lung cancer. It is important to discern which sampling method is the best from the image and patient condition to avoid the re‐genome biopsy. The special attitude as a genome biopsy for the success of the NGS analysis is required instead of the biopsy for the diagnosis until now.